Massive Oculomotor Nerve Enlargement: A Case of Presumed Schwannomatosis. (4th May 2017) - Donaldson, Laura; Rebello, Ryan; Rodriguez, Amadeo
ABSTRACT: A 45-year-old man presented with a slowly progressive pupil-involving third nerve palsy. Magnetic resonance imaging (MRI) revealed a tubular lesion extending from the interpeduncular cistern through the cavernous sinus and into the left orbit where it branched into a superior and an inferior division, clearly outlining the anatomy of the third cranial nerve. Multiple other, less pronounced, enlarged cranial nerves were noted. The differential diagnosis included chronic inflammatory demyelinating polyneuropathy (CIDP), hereditary motor and sensory neuropathy (HMSN), neurofibromatosis (NF), and schwannomatosis. The absence of other muscle weakness and of sensory symptoms combined with normal peripheral nerve conduction studies effectively ruled out the hypertrophic polyneuropathies and pointed to a syndromic cause of multiple benign peripheral nerve sheath tumours (PNSTs). The authors are treating this case as presumed schwannomatosis, a syndrome similar to NF2 with much lower frequency of acoustic neuromas.